Intimate Partner Violence Perpetrator Subtypes and their Developmental Origins: Implications for Prevention and Intervention. Issue 3 (15th September 2015) - Bernardi, Jessica; Day, Andrew
Abstract : Intimate partner violence (IPV) is a major issue for many Australian families and yet progress towards the development of effective prevention and behaviour change programs has been relatively slow. In this paper, it is proposed that the tendency to treat perpetrators as a homogenous group has hampered progress, and that treatment outcomes can be improved by tailoring treatment responses to a small set of personal and offence‐related characteristics. It explores the developmental origins and trajectories of these presentations and identifies some new directions for further research in this area.